Determination of Polar Heterocyclic Aromatic Amines in Meat Thermally Treated in a Roasting Bag with Dried Fruits - Sylwia Bulanda; Magdalena Szumska; Agnieszka Nowak; Beata Janoszka; Aleksandra Damasiewicz-Bodzek (Foods)
Frequent consumption of processed meat has been classified as carcinogenic to humans by the International Agency for Research on Cancer (Group 1), while red meat has been classified as probably carcinogenic (Group 2A). Mutagenic and carcinogenic compounds formed by heating in protein-rich food include, among others, heterocyclic aromatic amines (HAAs). Modifying the heat treatment of meat and using natural additives with antioxidant properties can lead to a reduction in their formation. The aim of this study was to determine polar HAAs (imidazoquinolines, IQ and MeIQ; imidazoquinoxalines, 8-MeIQx and 4,8-DiMeIQx; and phenylimidazopyridine, PhIP) in pork loin prepared without additives and with three types of dried fruit (apricots, cranberries, and prunes), baked in a roasting bag. HAAs were isolated from meat samples by solid-phase extraction. Quantitative analysis was performed by high-performance liquid chromatography with fluorescence detection (FLD) and a diode array detector (DAD). Only two HAAs, 8-MeIQx and PhIP, were detected in extracts isolated from meat samples. The total content of these compounds in meat roasted without additives was 5.9 ng/g. Using a dried fruit stuffing content of 200 g/kg of meat reduced these concentrations in dishes prepared with prunes, apricots, and cranberries by 42%, 47%, and 77%, respectively.